Phospholipases in arterial tissue: IV. The role of phosphatide acyl hydrolase, lysophosphatide acyl hydrolase, and sphingomyelin choline phosphohydrolase in the regulation of phospholipid composition in the normal human aorta with age - Eisenberg, S.; Stein, Y.; Stein, O. (The Journal of Clinical Investigation, 1969)
The role of phospholipases in the regulation of the changing phospholipid composition of normal human aortae with age was studied. Portions of grossly and histologically lesion-free ascending aortae from 16 females and 29 males obtained at autopsy, were analyzed for deoxyribonucleic acid (DNA), phospholipid, and cholesterol content and phospholipid composition. Enzymic activity toward four substrates, lecithin (LE), phosphatidyl ethanolamine, lysolecithin, and sphingomyelin (SP), was determined on portions of the same homogenate. By regression analysis for correlation between all determinations and age the following results were obtained: (a) total phospholipids and choleserol increased linearly with age; (b) the increase in sphingomyelin accounted for about 70% of the phospholipid increment; (c) hydrolysis of lecithin and phosphatidyl ethanolamine increased markedly with age, that of lysolecithin only moderately; (d) hydrolysis of sphingomyelin decreased with age; and (e) an inverse relation between the SP/LE ratio and age and sphingomyelinase/lecithinase activity and age was obtained. These results were interpreted to indicate that a causal relation exists between the fall in sphingomyelinase activity, both absolute and relative to lecithinase activity, and the accumulation of sphingomyelin with age.